The genome sequence of a pallopterid fly, Toxonevra muliebris (Harris, 1780) [version 1; peer review: 2 approved] - Gavin R. Broad; Maxwell V. L. Barclay; Olga Sivell (Wellcome Open Research)
We present a genome assembly from an individual male specimen of Toxonevra muliebris (pallopterid fly; Arthropoda; Insecta; Diptera; Pallopteridae). The genome sequence has a total length of 491.40 megabases. Most of the assembly (99.07%) is scaffolded into 6 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled and is 16.18 kilobases in length. Gene annotation of this assembly on Ensembl identified 21,433 protein-coding genes.